Household hazardous waste management: A review - Inglezakis, Vassilis J.; Moustakas, Konstantinos (Journal of Environmental Management, 2015)
Abstract This paper deals with the waste stream of household hazardous waste (HHW) presenting existing management systems, legislation overview and other relevant quantitative and qualitative information. European Union legislation and international management schemes are summarized and presented in a concise manner by the use of diagrams in order to provide crucial information on HHW. Furthermore, sources and types, numerical figures about generation, collection and relevant management costs are within the scope of the present paper. The review shows that the term used to refer to hazardous waste generated in households is not clearly defined in legislation, while there is absence of specific acts regulating the management of HHW. The lack of obligation to segregate HHW from the household waste and the different terminology used makes it difficult to determine the quantities and composition of this waste stream, while its generation amount is relatively small and, therefore, is commonly overlooked in waste statistics. The paper aims to cover the gap in the related literature on a subject that is included within the crucial waste management challenges at world level, considering that HHW can also have impact on other waste streams by altering the redox conditions or causing direct reactions with other non hazardous waste substances.
Keywords: Household hazardous waste; EU legislation; Hazardous waste; Waste; Separate collection; Waste management